An Updated Model Providing Long‐Term Data Sets of Energetic Electron Precipitation, Including Zonal Dependence. Issue 17 (12th September 2018) - van de Kamp, M.; Rodger, C. J.; Seppälä, A.; Clilverd, M. A.; Verronen, P. T.
Abstract: In this study 30‐ to 1, 000‐keV energetic electron precipitation (EEP) data from low Earth orbiting National Oceanic and Atmospheric Administration and MetOp Polar Orbiting Environmental Satellites were processed in two improved ways, compared to previous studies. First, all noise‐affected data were more carefully removed, to provide more realistic representations of low fluxes during geomagnetically quiet times. Second, the data were analyzed dependent on magnetic local time (MLT), which is an important factor affecting precipitation flux characteristics. We developed a refined zonally averaged EEP model, and a new model dependent on MLT, which both provide better modeling of low fluxes during quiet times. The models provide the EEP spectrum assuming a power law gradient. Using the geomagnetic index A p with a time resolution of 1 day, the spectral parameters are provided as functions of the L shell value relative to the plasmapause. Results from the models compare well with EEP observations over the period 1998–2012. Analysis of the MLT‐dependent data finds that during magnetically quiet times, the EEP flux concentrates around local midnight. As disturbance levels increase, the flux increases at all MLT. During disturbed times, the flux is strongest in the dawn sector and weakest in the late afternoon sector. The MLT‐dependent model emulates this behavior. The results of the models can be used to produce ionization rate data sets over any time period for which the geomagnetic A p index is available (recorded or predicted). This ionization rate data set will enable simulations of EEP impacts on the atmosphere and climate with realistic EEP variability. Key Points: A previously published model for radiation belt energetic electron precipitation has been updated and improved The model includes dependences on the following: the geomagnetic index A p, the L shell level relative to the plasmapause, and magnetic local time It provides the energy spectrum of 30‐ to 1, 000‐keV precipitating electron flux for any period of time where the geomagnetic index A p is supplied